Kinerja Pengolahan Air Limbah Domestik Terhadap Parameter Nitrat (NO₂⁻) dan Fosfat (PO₄³⁻) Dengan Metode Moving Bed Biofilm Reactor (MBBR) Di Instalasi Pengolahan Air Limbah (IPAL) Losari - Idris, M. Naufal Az Zarqan; Desi, Natsar; Chaerul, Muhammad (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study analyzes the performance of the Losari Wastewater Treatment Plant (IPAL) in reducing the levels of the pollutants Nitrite (NO2¯) and Phosphate (PO4³¯) in domestic wastewater using the Moving Bed Biofilm Reactor (MBBR) method. The issue of domestic waste in large cities, particularly in coastal areas like Losari, is becoming increasingly complex due to high population density and tourism activities, which require an effective waste treatment system that meets environmental quality standards. The main objective of this research is to analyze the chemical parameters (Nitrite and Phosphate) in the treatment of domestic wastewater using the MBBR method at the Losari wastewater treatment plant, as well as to analyze the optimization of wastewater treatment using this method. This research uses an observational method with a quantitative approach to measure the performance of MBBR in reducing pollutant levels, with wastewater samples taken from the inlet, MBBR tank, and outlet. The testing was conducted at the South Sulawesi Provincial Environmental Agency Laboratory. The test results show that the MBBR process is effective in reducing phosphate, with all testing points showing phosphate concentrations below the quality standard of 2 mg/L. However, for the nitrite parameter, although the levels at the inlet point are within the safe limits, there is an increase in levels at the outlet point (0.628 mg/L), which exceeds the quality standard of 0.6 mg/L, indicating that the nitrification-denitrification process is not yet optimal. Overall, the Losari wastewater treatment plant system with MBBR has successfully managed phosphate well, but further optimization is needed for nitrite processing to meet the established quality standards.